Preparticipation Screening of Athletes: The Prevalence of Positive Family History - Jiravska Godula, Bogna; Jiravsky, Otakar; Pesova, Petra; Jelinek, Libor; Sovova, Marketa; Moravcova, Katarina; Ozana, Jaromir; Hudec, Miroslav; Miklik, Roman; Hecko, Jan; Sknouril, Libor; Sovova, Eliska (Journal of cardiovascular development and disease, 2023)
Sudden cardiac death (SCD) is a leading cause of death among athletes, and those with a positive family history (FH) of SCD and/or cardiovascular disease (CVD) may be at increased risk. The primary objective of this study was to assess the prevalence and predictors of positive FH of SCD and CVD in athletes using four widely used preparticipation screening (PPS) systems. The secondary objective was to compare the functionality of the screening systems. In a cohort of 13,876 athletes, 1.28% had a positive FH in at least one PPS system. Multivariate logistic regression analysis identified the maximum heart rate as significantly associated with positive FH (OR = 1.042, 95% CI = 1.027-1.056, p < 0.001). The highest prevalence of positive FH was found using the PPE-4 system (1.20%), followed by FIFA, AHA, and IOC systems (1.11%, 0.89%, and 0.71%, respectively). In conclusion, the prevalence of positive FH for SCD and CVD in Czech athletes was found to be 1.28%. Furthermore, positive FH was associated with a higher maximum heart rate at the peak of the exercise test. The findings of this study revealed significant differences in detection rates between PPS protocols, so further research is needed to determine the optimal method of FH collection.
Keywords: preparticipation screening; sudden cardiac death; athlete